Purification and Characterization of Novel Antioxidative Peptides From Duck Liver Protein Hydrolysate as Well as Their Cytoprotection Against Oxidative Stress in HepG2 Cells - Sun, Jin; Zhou, Changyu; Cao, Jinxuan; He, Jun; Sun, Yangying; Dang, Yali; Pan, Daodong; Xia, Qiang (Frontiers in Nutrition, 2022)
This study aimed at mining antioxidant peptides derived from duck liver as a strategy for valorizing poultry byproducts utilization via the isolation and characterization of peptide molecules with great antioxidant potential and cytoprotective effects against hydrogen peroxide-induced oxidative stress. Six novel peptides, including GEHGDSSVPVWSGVN, HLDYYLGK, HLTPWIGK, DTYIRQPW, WDDMEKIWHH, and MYPGIAD were isolated and purified by Sephadex G-15 and reverse-phase high-performance liquid chromatography, followed by the identification with liquid chromatography-tandem mass spectrometry. Among the hydrolytes from different enzymes, the alcalase-originated peptides presented the strongest antioxidant capacity as revealed by DPPH and ABTS assays. The synthesized peptides were used to validate the antioxidant activities, identifying that DTYIRQPW and WDDMEKIWHH were the major antioxidative peptides capable of protecting HepG2 cells from H2O2-induced oxidative damage via stimulating antioxidant enzymes such as superoxide dismutase and catalase to eliminate free radicals and to decrease lipid peroxidation products. Molecular docking suggested that the antioxidative properties of the isolated peptides were related to the site and number of hydrogen bonds. This investigation indicated the great potential of duck liver protein hydrolysates as a base material for producing and developing dietary bioactive peptides.